The Transmission of Culture in Rural Multigenerational Family : Problem of Digital Exclusion and Distance Between Generations - Czykier, Krzysztof (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Text raises an issue of transmission of culture in multigenerational rural families (generations young, average and older) in context of digital exclusion and distance between generations.